Penerapan Metode TOPSIS Dalam Sistem Pendukung Keputusan Kelayakan Penerima Pinjaman Kredit - Agus Iskandar (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
In determining the eligibility of loan recipients at Finance companies, it is carried out with the approval of the Head Office, then the stage of checking customer data is carried out with the approval of the office manager. Furthermore, in analyzing the decision-making eligibility of customers receiving credit loans, using a manual system that takes a long time, therefore, a decision support system is needed that functions to minimize excess or lack of data. In this study, it will be explained how the process of determining alternative credit recipient customers applies the TOPSIS method. The research results will produce the highest ranking value which will be determined as the highest alternative. The data used in this study are 10 alternative data samples using 5 criteria, so that the results of calculations that have been carried out using 8 alternatives and 5 criteria produce the best alternative, namely alternative A2 above with a value of 0.848 as a recommendation for a customer who will be entitled to receive a loan from finance company.